Effect of the Spiritist passe energy therapy in reducing anxiety in volunteers: A randomized controlled trial - de Souza Cavalcante, Ricardo [UNESP]; Banin, Vanessa Burgugi [UNESP]; de Moura Ribeiro Paula, Niura Aparecida [UNESP]; Daher, Solange Ramires [UNESP]; Habermann, Marta Cassoni [UNESP]; Habermann, Francisco [UNESP]; Bravin, Ariane Moyses [UNESP]; da Silva, Carlos Eduardo Capelasso [UNESP]; de Andrade, Luis Gustavo Modelli [UNESP] (Elsevier, 2016)
Background: In Brazil, one of the most used energy therapies is the Spiritist passe, which is practiced by Spiritist healers. Although experimental studies have demonstrated the effectiveness of different energy therapies in reducing anxiety and pain, little is known about the effect of the Spiritist passe on health outcomes. Therefore, the present study aimed at evaluating the effectiveness of passe energy therapy in reducing anxiety symptoms. Methods/design: In this prospective, randomized controlled trial, participants were randomly allocated into two groups: Intervention (8 weekly Spiritist passe sessions, n = 23), and Control (8 weekly sham Spiritist passe sessions, n = 27). Anxiety was assessed using the Trait Anxiety Inventory (STAI-trait). Results: Of 97 individuals screened, 50 were included in the final analysis. Decreasing STAI-trait anxiety scores were observed in both groups throughout the study (p < 0.0001). By the end of the study, 17% and 63% of intervention and control participants, respectively, still met the criterion for anxiety (p = 0.001). However, anxiety reduction was more accentuated in the Spiritist passe group (p = 0.02). Conclusion: In this small pilot study, anxiety was more markedly reduced in participants receiving the Spiritist passe than in controls, warranting larger trials. Trial Registration: NCT02376959.
Keywords: Anxiety; Complementary therapies; Energy therapies; Spiritism; Spiritual healing; Therapeutic touch